The PENGARUH KOMUNIKASI INSTRUKSIONAL TUTOR TERHADAP MOTIVASI BELAJAR SISWA DI LEMBAGA KURSUS ENGLISH TIME INDONESIA - Ferbyana, Alma (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2025)
The importance of instructional communication in the context of English language learning at English Time Indonesia in Kabupaten Purwakarta, Indonesia, is highlighted in this research. The study is motivated by changes in teaching approaches and the need to enhance student learning motivation through effective interaction between tutors and students. This study employs a quantitative method by surveying 109 students from various levels at English Time Indonesia. Data were collected through questionnaires regarding instructional communication and students' learning motivation. The research findings indicate that instructional communication positively influences students' learning motivation. Statistical analysis reveals that instructional communication accounts for approximately 35.3% of the variance in students' learning motivation at the institution. These findings are consistent with previous literature emphasizing the crucial role of interpersonal communication in enhancing learning quality.